2014
DOI: 10.1371/journal.pone.0085001
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Carriage in Sub-Saharan Africa—A Systematic Review

Abstract: BackgroundPneumococcal epidemiology varies geographically and few data are available from the African continent. We assess pneumococcal carriage from studies conducted in sub-Saharan Africa (sSA) before and after the pneumococcal conjugate vaccine (PCV) era.MethodsA search for pneumococcal carriage studies published before 2012 was conducted to describe carriage in sSA. The review also describes pneumococcal serotypes and assesses the impact of vaccination on carriage in this region.ResultsFifty-seven studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
56
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 75 publications
17
56
6
Order By: Relevance
“…In a systematic review on pneumococcal carriage in Sub-Saharan Africa[10], carriage rates varied widely between 21–94%, but in the meta-analysis used, carriage rates (63%) were similar to those in our study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In a systematic review on pneumococcal carriage in Sub-Saharan Africa[10], carriage rates varied widely between 21–94%, but in the meta-analysis used, carriage rates (63%) were similar to those in our study.…”
Section: Discussionsupporting
confidence: 83%
“…A range of 35–93% of healthy children aged under five years in low-income countries has been shown to be colonized with pneumococci in the nasopharynx [9,10]. Pneumococcal conjugate vaccine (PCV) reduces vaccine-type pneumococcal carriage and thereby the dynamics of serotype transmission and pneumococcal disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we did not include upper-middle income countries in the analysis even though some populations within these countries may share characteristics with populations in low or lower-middle income countries. For instance, in one study in South Africa, prevalence of pneumococcal carriage was high (22.5%–61.0%) in children younger than five years of age [112], whereas a study in Costa Rica showed that infants acquire nasopharyngeal carriage of S. pneumoniae at a rate (3.1% at one month of age and 19.4% at one year of age) comparable to that seen in developed countries [113].…”
Section: Discussionmentioning
confidence: 95%
“…Three were PCV9 trials 29,32,37 and 1 was a PCV10 trial. 26,27 We were unable to restrict the latter to PCV7 serotypes only (as all data for PCV10 serotype were aggregated), and we explored the sensitivity of our model output to including (or not) data from that study. Nine data points were from surveys after booster vaccination (Table 1).…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
“…Finally, overall and booster schedule VE C estimates and respective model coefficients were similar with and without data from the PCV10 trial. 26,27 We explored 2 other models of waning, in addition to the main model (Appendix, Supplemental Digital Content 2, http:// links.lww.com/INF/C159). In all 3 models, there was good evidence of protective efficacy in the first few years after vaccination.…”
Section: Sensitivity Analysismentioning
confidence: 99%